Incidentally detected hydatid cyst of the adrenal gland: A case report - Akbulut, S (2016)
Hydatid cysts are a zoonotic disease that can involve many organs and tissues in the human body but primarily involve the liver and lungs. Of the main organs, adrenal glands are those seldom affected by hydatid cysts. The purpose of this study was to present a case with an incidentally detected hydatid cyst of the right adrenal gland on computed tomography, and a positive echincoccus IgG enzyme-linked immunosorbent assay test on top of a toxic multinodular thyroid goiter for which thyroidectomy was indicated. C1 [Akbulut, Sami] Inonu Univ, Dept Surg, Fac Med, Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Liver Transplant Inst, Fac Med, Malatya, Turkey.